Affordances for practice in CRM : A critical realist approach - Tuomisto, Noora (My University, 2019)
As digitalization sweeps through workplaces, the academics have been intrigued by the theory of sociomateriality to better explain the dynamic, emergent and entangled consequences of the technologies on contemporary organizing and work practices. Sociomateriality, connoting the ontological inseparability of the material and the social, emerged to challenge the various dichotomies in information systems research by employing an agential realist stance. Later, this line of inquiry has been utilized alongside multiple theories in organization, management and sociological studies in order to understand how matter matters in organizational life. Simultaneously, its ontological base has expanded – a critical realist approach to sociomateriality arose from the criticism on the relational view on humans and artifacts. This study has been conducted from the critical realist approach to understand how a customer relationship management (CRM) system matters to strategy. It utilizes the practice-based approach, namely strategy-as-practice and the affordance approach to explain how a new customer-oriented strategy can be enacted through the interplay between the old and new technologies as well as the customer-facing employees. The thesis takes place in a case study environment, employing qualitative methods such as observation and semi-structured interviews. The case company is an occupational healthcare provider in Finland. The study identified the following constraints that trigger organizational change and lead to new technology implementation and new practices in customer relationship management: data inconsistency, routine discrepancy and relationship erosion. The perceived affordances post-dating the constraints were knowledge diffusion, management and controlling, workflow integration as well as analysis and development. Affordances are experienced in all levels of the organization.
Keywords: sociomateriality; customer relationship management; affordances; strategy-as-practice; fi=Johtaminen ja organisaatiot|en=Management and Organization|; Master’s Programme in Strategic Business Development